An analysis-oriented parameter extraction method for features on freeform surface. (September 2019) - Li, Jixing; Ning, Tao; Xi, Ping; Hu, Bifu; Wang, Tian
The features on freeform surface are common in products with complex curved surfaces, such as gas film holes attached on turbine blade surface or pressing head on the multi-spots bending press. The freeform surfaces generally have tiny geometric structure, the large number and regular arrangement, which makes it hard to extract analysis parameters from CAD structures and construct equivalent analysis features. Therefore, the analysis models generation will be accelerated if parameters for analysis could be extracted automatically rather than manually. In this paper, the analysis-oriented parameter extraction problem is proposed and analyzed. The geometry pattern parameter and physical attribute parameter are summarized and defined as the research kernel based on common analysis scenarios. Based on Hough transform and k -means clustering method, a geometry pattern parameter extraction method is proposed, which can convert analytic criterion of extraction requirements into clear pattern recognition problems. A physical attribute parameter extraction method based on rule reasoning is also put forward to extract numeric analysis parameters with physical meanings. Finally, two representative cases are taken to illustrate the implementation steps of the proposed method, and to verify the effectiveness and practicability in engineering. The instance demonstrates that the proposed method could significantly reduce the time consumption of analysis model generation and improve the integration degree of CAD/CAE.